Challenges and interpersonal dynamics during a two-person lunar analogue Arctic mission - Marques-Quinteiro, Pedro; Käosaar, Andres; Delben, Paola Barros; Kjærgaard, Anders; Leon, Gloria R. (Frontiers in Astronomy and Space Sciences, 2023)
This case study was designed as an analogue for aspects of NASA’s planned Artemis missions to the lunar surface. The specific aims were to examine emerged mission challenges and dyadic affective and process dynamics over the course of a three-month lunar habitat analogue Arctic mission. Participants were two men who also had key roles in designing the habitat. Pre- and post- expedition interviews were conducted and daily satellite phone messages to mission control over the three-month mission were assessed. An integrated mixed methods approach was used to analyze challenges, group affect, and group processes, with the goal of furthering the understanding of coping and psychosocial work experiences in challenging conditions. The findings indicated that different challenges took distinct temporal trajectories across mission phases; based on the relational themes, several challenges were identified, primarily physical challenges related to the experience of coping in an ICE environment, and psychosocial challenges associated with the preparation and execution of mission tasks. Physical challenges, positive tone, and action processes were the themes most connected to each other. To deal with these challenges, the team adapted by more frequently engaging in action and transition processes. The specific training for the mission the participants engaged in, and prior knowledge about each other enabled team members to deal with mission exigencies while maintaining a positive outlook. Fostering strong positive relationships was an important mechanism to build resilience and effective performance while under ongoing, extreme conditions.